Phase IV, Open-Label, Safety Study Evaluating the Use of Dexmedetomidine in Pediatric Patients Undergoing Procedure-Type Sedation - Jooste, Edmund H.; Hammer, Gregory B.; Reyes, Christian R.; Katkade, Vaibhav; Szmuk, Peter (Frontiers in Pharmacology, 2017)
Dexmedetomidine (Precedex™) may be used as an alternative sedative in children, maintaining spontaneous breathing and avoiding tracheal intubation in a non-intubated moderate or deep sedation (NI-MDS) approach. This open-label, single-arm, multicenter study evaluated the safety of dexmedetomidine in a pediatric population receiving NI-MDS in an operating room or a procedure room, with an intensivist or anesthesiologist in attendance, for elective diagnostic or therapeutic procedures expected to take at least 30 min. The primary endpoint was incidence of treatment-emergent adverse events (TEAEs). Patients received one of two doses dependent on age: patients aged ≥28 weeks’ gestational age to <1 month postnatal received dose level 1 (0.1 µg/kg load; 0.05–0.2 µg/kg/h infusion); those aged 1 month to <17 years received dose level 2 (1 µg/kg load; 0.2–2.0 µg/kg/h infusion). Sedation efficacy was assessed and defined as adequate sedation for at least 80% of the time and successful completion of the procedure without the need for rescue medication. In all, 91 patients were enrolled (dose level 1, n = 1; dose level 2, n = 90); of these, 90 received treatment and 82 completed the study. Eight patients in dose level 2 discontinued treatment for the following reasons: early completion of diagnostic or therapeutic procedure (n = 3); change in medical condition (need for intubation) requiring deeper level of sedation (n = 2); adverse event (AE; hives and emesis), lack of efficacy, and physician decision (patient not sedated enough to complete procedure; n = 1 each). Sixty-seven patients experienced 147 TEAEs. The two most commonly reported AEs were respiratory depression (bradypnea; reported per protocol-defined criteria, based on absolute respiratory rate values for age or relative decrease of 30% from baseline) and hypotension. Four patients received glycopyrrolate for bradycardia and 7 patients received intravenous fluids for hypotension. SpO2 dropped by 10% in 2 patients, but resolved without need for manual ventilation. All other reported AEs were consistent with the known safety profile of dexmedetomidine. Two of the 78 patients in the efficacy-evaluable population met all sedation efficacy criteria. Dexmedetomidine was well tolerated in pediatric patients undergoing procedure-type sedation. clinicaltrials.gov identifier: NCT01519167; https://clinicaltrials.gov/ct2/show/NCT01519167